Attitude Towards Artificial Intelligence and Personality Traits among Research Scholars - Dr. S. JEYA BHARATHI; T. ELIZABETH REGINA; S. VISWA PRIYA (The Bioscan, 2026)
Artificial intelligence can be defined as the capability of a device to perform functions that are normally associated with human intelligence, such as reasoning, learning, and self-improvement (Willick, 1983). Personality is the dynamic organization within the individual of those psychophysical systems that determine his unique adjustments to his environment (Gordon Allport, 1937). Attitudes toward AI among research scholars are likely shaped by a combination of their professional environment, personal experiences, and personality traits. This study aims to examine attitudes towards AI and personality traits among research scholars. It includes a sample of 100 research scholars. The tools employed in the study are Attitude Towards AI (AAI) and the Big Five Personality Inventory (BFI). Results suggest that there is a positive significant relationship between attitude towards AI and personality traits and it is strongly correlated with agreeableness personality trait (r = 0. 97, **p < 0.01). It can be suggested that personality traits shape how individuals evaluate the usefulness, risks, and ethical implications of AI, impacting their acceptance and adoption of AI technologies.